Поняття системи та структури адвокатури України - Бандурка, С. С.; Bandurka, S. S. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. - 2024. - № 1. - С. 82-89, 2024)
Розглянуто поняття соціальної системи взагалі та системи адвокатури зокрема. Охарактеризовано окремі елементи структури адвокатури – складової цілісного комплексу адвокатури як недержавного самоврядного інституту, що забезпечує здійснення захисту, представництва та надання інших видів правової допомоги на професійній основі. Досліджено структуру адвокатури в її взаємозв’язку та організаційній єдності, що забезпечує принцип самостійного вирішення питання організації і діяльності адвокатури відповідно до законодавства. Зазначено, що правову основу здійснення адвокатської діяльності складають: Конституція України, Закон України «Про адвокатуру та адвокатську діяльність», Кримінальний процесуальний кодекс України, Кодекс адміністративного судочинства України, Цивільний процесуальний кодекс України, інші кодекси та закони України, Правила адвокатської етики та інші нормативно-правові акти, що тією чи іншою мірою регламентують захист прав і свобод людини і громадянина та законних інтересів юридичних осіб в Україні. Аргументовано, що адвокатура України виконує роль єдиного незалежного недержавного самоврядного інституту, що забезпечує захист прав і свобод людини і громадянина та законних інтересів суспільства і державних органів на принципах верховенства права, законності, незалежності, конфіденційності та уникнення конфлікту інтересів.

The article examines the concept of the social system in general and the legal system in particular. Separate elements of the structure of the bar are characterized as components of the whole complex of the bar as a non-state self-governing institution that ensures the implementation of representation protection and the provision of other types of legal assistance on a professional basis. The structure of the bar in its interrelationship and organizational unity, which ensures the principle of independent resolution of the issue of the organization and activity of the bar in accordance with the law, is studied. It is shown that the legal basis for the practice of advocacy is the Constitution of Ukraine, the Law of Ukraine "On Advocacy and Advocacy", the Criminal Procedure Code of Ukraine, the Code of Administrative Procedure of Ukraine, the Civil Procedure Code of Ukraine, other codes and laws of Ukraine, the Rules of Advocate Ethics and regulatory legal acts that, to one degree or another, regulate the protection of human and citizen rights and freedoms and the legal interests of legal entities in Ukraine. It is argued that the Bar of Ukraine fulfills the role of a single independent non-state selfgoverning institution that ensures the protection of human and citizen rights and freedoms and the legitimate interests of society and state bodies based on the principles of rule of law, legality, independence, confidentiality and avoidance of conflict of interests. The role of the bar in the protection of human rights and freedoms during war is growing in connection with a significant increase in victims of military operations, shelling and bombing of the civilian population, loss of relatives and loved ones.

Рассмотрено понятие социальной системы и системы адвокатуры в частности. Охарактеризованы отдельные элементы структуры адвокатуры – составляющей целостного комплекса адвокатуры как негосударственного самоуправляющегося института, обеспечивающего осуществление защиты, представительства и других видов правовой помощи на профессиональной основе. Исследовано структуру адвокатуры в ее взаимосвязи и организационном единстве, что обеспечивает принцип самостоятельного решения вопроса организации и деятельности адвокатуры в соответствии с законодательством.
Concepts of the system and structure of the bar of Ukraine
Keywords: адвокатура; адвокатська діяльність; система; структура адвокатури; захист прав і свобод; надання правової допомоги; bar; advocacy; system; structure of advocacy; protection of rights and freedoms; provision of legal assistance; адвокатская деятельность; структура адвокатуры; защита прав и свобод; предоставление правовой помощи